2020
DOI: 10.3389/feduc.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Home Education During the COVID-19 Lockdown in the Czech Republic: A Rapid Survey of 1st-9th Graders' Parents

Abstract: Schools have been closed in many countries due to the on-going COVID-19 pandemic, but education continues online. Little is known about how parents cope with educating their children in this unprecedented situation. Here, we present the results of a rapid survey examining the experience of Czech parents of children in Grades 1-9 (Age ∼ 6-15; N = 9,810) with respect to home education during the COVID-19 lockdown. This survey was distributed widely, but only online and parents participated voluntarily. Mainly fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 5 publications
(4 reference statements)
6
58
0
9
Order By: Relevance
“…Esposito and Principi (2020) highlighted alternative strategies, such as reducing class size or physical distancing, considering the adverse effects of school closure on children and their families (e.g., the economic consequences for parents who remain at home to take care of their children, or problems in implementing distance learning in the poorest areas of some countries). However, a recent study examining parents of Czechia children show that families tend to cope well with education at home during the COVID-19 confinement, although they consider that children would need more time for learning activities (Brom et al, 2020). This is the first time that a quarantine to control a pandemic has been implemented in Italy and Spain, as well as in most countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Esposito and Principi (2020) highlighted alternative strategies, such as reducing class size or physical distancing, considering the adverse effects of school closure on children and their families (e.g., the economic consequences for parents who remain at home to take care of their children, or problems in implementing distance learning in the poorest areas of some countries). However, a recent study examining parents of Czechia children show that families tend to cope well with education at home during the COVID-19 confinement, although they consider that children would need more time for learning activities (Brom et al, 2020). This is the first time that a quarantine to control a pandemic has been implemented in Italy and Spain, as well as in most countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Given the unprecedented nature of the COVID-19 pandemic and widespread lockdown, it is important to gather empirical evidence relating to the potential psychological effects of the current crisis on very young children and their families. Published empirical research of the effects on families is just beginning to emerge (e.g., Brom, et al, 2020;Spinelli, et al, 2020). For example, Spinelli et al (2020) reported findings from data gathered during lockdown in Italy from parents, and found that parental stress and perceptions of quarantine were associated with children's behavioural and emotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…Deskriptivní analýzy získaných kvantitativních dat (Brom et al, 2020a(Brom et al, , 2020b poskytly informace o tom, kolik času tráví žáci aktuálně školní prací, jaké pomoci se jim dostává od rodičů a zda jsou úkoly, které dostávají ze školy, z pohledu rodičů přiměřené. Výsledky napověděly, že u respondentů výzkumu nezpůsobuje vzdělávání doma žádné větší problémy.…”
Section: Výzkumný Problém a Výzkumné Otázkyunclassified
“…Ve výzkumném souboru byly zastoupeny vyšší měrou případy dětí, kde aspoň jeden z rodičů/vychovatelů dosáhl vysokoškolského vzdělání. Tyto případy tvořily v souboru 60 %, přičemž odhadovaný podíl v populaci dětí v povinném vzdělání je 40 % (Brom et al, 2020a(Brom et al, , 2020b. Na základě statistické analýzy našich dat jsme však záhy zjistili, že vzdělání rodičů mezi odpověďmi příliš nediferencovalo.…”
Section: Limity Studieunclassified